OPTIMISING THE FUNCTIONALITY OF THE BASEMENT PRAYER ROOM AT LAWU PLAZA MADIUN MALL: A REVIEW OF VISITOR SATISFACTION USING A DESIGN THINKING APPROACH - Bintang Mahendra Erwandaru; Salsabila Zashika Rizki; Didit Widiatmoko Soewardikoen; Ahmad Sidiq; Ghifari Aqsha Syuhada (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study investigated visitor satisfaction and design difficulties at the Basement Prayer Room of Mall Lawu Plaza, Madiun City. A Prayer Room on the mall's ground floor signifies incorporating religious components into the corporate environment, showcasing the mall's capacity to blend traditional religious activities with a contemporary setting. This project intends to make substantial theoretical and practical advancements by thoroughly examining visitor requirements in unconventional prayer environments. This research method is a form of Design thinking research, which is the primary approach. The study’s findings indicated that observations and interviews identified several obstacles impacting the visitor experience, such as spatial limitations, privacy concerns, insufficient illumination, and ventilation issues. The proposed remedies, rooted in Design Thinking principles, consist of recommendations for artificial ventilation, alteration of wall materials, enlargement of prayer spaces, extra storage, and potential relocation of the mall. The solutions focus on enhancing the prayer space's comfort, inclusivity, and functionality by following human-centred design principles. This study highlights the requirement to incorporate human requirements and experiences into the Design of places of worship in modern metropolitan settings.